ABIN-1 regulates RIPK1 activation by linking Met1 ubiquitylation with Lys63 deubiquitylation in TNF-RSC. Issue 1 (January 2018) - Dziedzic, Slawomir; Su, Zhenyi; Jean Barrett, Vica; Najafov, Ayaz; Mookhtiar, Adnan; Amin, Palak; Pan, Heling; Sun, Li; Zhu, Hong; Ma, Averil; Abbott, Derek; Yuan, Junying
Abstract Ubiquitylation of the TNFR1 signalling complex (TNF-RSC) controls the activation of RIPK1, a kinase critically involved in mediating multiple TNFα-activated deleterious events. However, the molecular mechanism that coordinates different types of ubiquitylation modification to regulate the activation of RIPK1 kinase remains unclear. Here, we show that ABIN-1/NAF-1, a ubiquitin-binding protein, is recruited rapidly into TNF-RSC in a manner dependent on the Met1-ubiquitylating complex LUBAC to regulate the recruitment of A20 to control Lys63 deubiquitylation of RIPK1. ABIN-1 deficiency reduces the recruitment of A20 and licenses cells to die through necroptosis by promoting Lys63 ubiquitylation and activation of RIPK1 with TNFα stimulation under conditions that would otherwise exclusively activate apoptosis in wild-type cells. Inhibition of RIPK1 kinase and RIPK3 deficiency block the embryonic lethality ofAbin-1 –/– mice. We propose that ABIN-1 provides a critical link between Met1 ubiquitylation mediated by the LUBAC complex and Lys63 deubiquitylation by phospho-A20 to modulate the activation of RIPK1. Dziedzic et al. show that the ubiquitin-binding protein ABIN-1 is recruited into TNFR1 signalling complex in a manner dependent on Met1 -ubiquitinating complex LUBAC to regulate K63 de-ubiquitination to activate RIPK1.